Do female audit committee characteristics influence audit fees? Evidence from the UK - Naila Amara; Saad Bourouis; Sajead Mowafaq Alshdaifat; Houssam Bouzgarrou; Hany Elbardan (Problems and Perspectives in Management)
This study examines the effect of female representation on audit fees in listed UK companies, concentrating on the demographic characteristics of female directors, specifically age and nationality. Using a sample of 165 FTSE 350 companies from 2011 to 2021, generalized least squares regression models are employed to test the link between female audit committee members and audit fees from both the demand and supply sides. The results show a negative relationship between the proportion of females on audit committees and audit fees with a coefficient of –0.2273 (p < 0.05). Thus, higher female representation tends to lower audit costs. However, when considering demographic characteristics, the age and nationality of female members have a positive effect on audit costs, with coefficients of 0.0145 (p < 0.01) and 0.5546 (p < 0.01), respectively. Thus, while gender diversity reduces audit costs overall, experienced (older) female directors and those from diverse national backgrounds may add to audit complexity and, therefore, increase fees. The implications of these findings are relevant to policymakers and corporate governance bodies. Diversity policies should go beyond simple gender quotas. Instead, they should include a broader set of demographic attributes when promoting female representation on audit committees to achieve audit quality and cost efficiency. AcknowledgmentThis study received full funding from the Middle East University, Amman, Jordan.